2011
DOI: 10.1007/s11738-011-0780-2
|View full text |Cite
|
Sign up to set email alerts
|

Plant peroxidases: biomarkers of metallic stress

Abstract: The term ''peroxidase'' designs a group of hemoproteins with a wide structural variability. These enzymes catalyze the redox reaction between hydrogen peroxide and some reductors. They can be found in animals, plants and microorganisms. In plants, peroxidases are involved in numerous cellular processes such as development and stress responses. In fact, they are involved in growth regulation by controlling hormonal and cell wall metabolism and antioxidant defense. On the other hand, these enzymes are considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(43 citation statements)
references
References 53 publications
5
32
0
1
Order By: Relevance
“…na -not analyzed, measured values below detection limit, BDL -below detection limit (0.48 ng·kg -1 for As) and between the plants grown on the three types of soil, according to the C-A-B grouping except for those grown on soils U and C 1 I (Table 7). In agreement with our results, Contreras et al [49], Jouili et al [50], and Arunakumara et al [51] demonstrated that, when the concentration of HM is changed, the plants produce a different content of lipid peroxidation, which leads to the damage of the biological molecules. In conclusion, the excess of metals involves the induction of lipid peroxidation in plants, which causes the degradation of lipoprotein membrane by lipid peroxidation, which could also include the degradation of photosynthetic pigments, causing deterioration in growth [52].…”
Section: Resultssupporting
confidence: 93%
“…na -not analyzed, measured values below detection limit, BDL -below detection limit (0.48 ng·kg -1 for As) and between the plants grown on the three types of soil, according to the C-A-B grouping except for those grown on soils U and C 1 I (Table 7). In agreement with our results, Contreras et al [49], Jouili et al [50], and Arunakumara et al [51] demonstrated that, when the concentration of HM is changed, the plants produce a different content of lipid peroxidation, which leads to the damage of the biological molecules. In conclusion, the excess of metals involves the induction of lipid peroxidation in plants, which causes the degradation of lipoprotein membrane by lipid peroxidation, which could also include the degradation of photosynthetic pigments, causing deterioration in growth [52].…”
Section: Resultssupporting
confidence: 93%
“…CAT is another major antioxidant enzyme that protects plant cells from hydrogen peroxide (Witlekens et al, 1995). POD is a multifunctional and ubiquitous enzyme found in plants, and is involved in numerous cellular processes such as development and stress responses (Jouili et al, 2011). These antioxidant enzyme activities change markedly in response to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The different enzyme reactions might be explained by their specific physiological roles. The reduction of H 2 O 2 to water is regarded as a secondary function of GPO in plants, while its main role is related to the oxidation of diverse substrates, thus playing a central role in controlling the cell wall biogenesis and in regulating its function, as well as in controlling the hormonal metabolism (De Gara et al 2010;Jouili et al 2011). On the other hand, the main physiological role of the two other enzymes evaluated in this study is supposed to be the elimination of excess H 2 O 2 .…”
Section: Separate Effect Of Excess Coppermentioning
confidence: 99%
“…Generally, the activity of one or more antioxidant enzymes is increased under metal stress and under excess Cu, in particular; however, contradictory effects have been observed. The enzyme reaction depends on enzyme type; plant species, variety, organ and prehistory; stress strength and duration; and environmental conditions (Luna et al 1994;Mazhoudia et al 1997;Zhao et al 2010;Jouili et al 2011). After pathogen recognition, both activation and deactivation of different scavenging systems have also been reported (Mehdy 1994;Torres et al 2006).…”
Section: Introductionmentioning
confidence: 99%